Perspektif Patronase Edward Aspinal dalam Proses Pemenangan Busyro Karim Sebagai Bupati Dua Periode di Kabupaten Sumenep - Roiyan, Ahlur (Jurnal Review Politik, 2023)
This research was conducted to find out about the pattern of leadership built by Busyro Karim so that he could win the regional election for two terms in Sumenep district, Madura. In addition, this research also proves that there are power relations that are formed in society, both in general and the community elites who are in government. In addition, there is also a patron-client relationship during the election process for the Regent. Based on the issues raised, researchers used the theory of patronage as a research analysis scalpel. This research is descriptive in nature which is taken from some data as material for analyzing data. The data was taken through interviews and literature review contained in the qualitative method. The results of the study found that there was a power relation that was formed in the process of selecting Bustro Karim as Regent for Two Periods, besides that there was also a patronage relationship in the process of selecting a Regent